System Center Configuration Manager reporting unleashed - Jones, Garth; Toll, Dan; Meyler, Kerrie (Sams, 2016)
Microsoft System Center Configuration Manager's SQL Server database contains valuable information about your users, computers, hardware, operating systems, applications, compliance status, and much more. Microsoft has provided excellent tools for extracting this information in meaningful ways, including SQL Server Reporting Services (SSRS) and SQL Server Data Tools Business Intelligence (SSDT-BI). System Center Configuration Manager Reporting Unleashed shows you how to make the most of these tools. World-renowned System Center reporting guru Garth Jones and his expert coauthors guide you through all facets of custom reporting with System Center. You'll walk through installing and configuring SSRS, using SQL views to find the data you need, writing SQL queries, creating basic and advanced reports, and using role-based administration to securely deliver those reports to the correct individuals. Jones brings together reliable, comprehensive, and up-to-date System Center reporting techniques you'll find in no other book or website. Using this guide, you can consistently retrieve the right information to solve immediate problems and quickly respond to management concerns. Detailed information on how to: Install and configure SQL SSRS for optimal System Center reporting and easier troubleshooting; Understand the data stored in the ConfigMgr site database; Efficiently retrieve ConfigMgr data by writing SQL queries in SQL Server Management Studio; Learn best practices for developing and designing System Center reports; Create report templates, customize content with report parameters, and embed charts; Customize logos, color palettes, and other report elements for your own organization; Construct advanced drillthroughs to provide deeper understanding; Strengthen report security by integrating ConfigMgr role-based administration into SQL queries; Leverage reporting to measure KPIs and gain a better understanding of your environment; Tailor your reports to the needs of end-users or management; Foreword by Wally Mead, Principal Program Manager, Cireson. The only book entirely dedicated to Configuration Manager reporting, this guide complements Meyler's System Center 2012 Configuration Manager Unleashed, offering far more in-depth coverage of reporting than the single chapter in that book. Most of the content in this new guide will be equally valuable in both System Center 2016 and 2012 environments.
Includes index. - Online resource; title from title page (Safari, viewed April 22, 2016)
Keywords: Microsoft System center configuration manager; Computer networks -- Management -- Computer programs; Software configuration management -- Computer programs; Microsoft system center configuration manager; Réseaux d'ordinateurs; Gestion; Logiciels; Logiciels; Gestion de configurations; Logiciels; COMPUTERS; Management Information Systems; COMPUTERS; Networking; General